2020
DOI: 10.21037/cdt.2020.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2, Galectin-3 and clinical prognosis of patients with hypertrophic cardiomyopathy undergoing ventricular septal myectomy: a correlation analysis

Abstract: Background: Hypertrophic cardiomyopathy (HCM) is the most common chromosomal abnormal heart disease. The pathophysiological mechanism of HCM is complex. Several studies have suggested that the level of Soluble ST2 (sST2) may be a biomarker of chronic systolic heart failure, however, the role of sST2 in HCM remains unclear. So we performed this study to analyze the role of Soluble ST2 (sST2), and its correlations with clinical prognosis of patients with hypertrophic cardiomyopathy (HCM) undergoing ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Inhibition of the Gal-3 pathway, which is currently one of the most promising novels therapeutic targets for managing myocardial fibrosis, may prevent cardiac remodeling and dysfunction In the preclinical study ( 54 ). Furthermore, previous clinical research has shown that Gal-3 as a biomarker is correlated with CV disease risk stratification ( 55 ) or adverse prognosis ( 52 , 56 ). In the field of HF, Gal-3 has proven to provide additive diagnostic and prognostic value ( 57 , 58 ) and was recommended as a novel biological indicator for the risk stratification of HF at the 2013 American College of Cardiology Foundation (ACCF) /American Heart Association (AHA) ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the Gal-3 pathway, which is currently one of the most promising novels therapeutic targets for managing myocardial fibrosis, may prevent cardiac remodeling and dysfunction In the preclinical study ( 54 ). Furthermore, previous clinical research has shown that Gal-3 as a biomarker is correlated with CV disease risk stratification ( 55 ) or adverse prognosis ( 52 , 56 ). In the field of HF, Gal-3 has proven to provide additive diagnostic and prognostic value ( 57 , 58 ) and was recommended as a novel biological indicator for the risk stratification of HF at the 2013 American College of Cardiology Foundation (ACCF) /American Heart Association (AHA) ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is primarily secreted by activated macrophages during myocardial stress and stimulates fibroblasts to deposit collagen into the extracellular matrix ( 50 ), initiating the pro-fibrotic progression of the myocardium ( 51 ). Song et al ( 52 ) and Yakar Tuluce et al ( 53 ) found a connection between Gal-3 levels and the degree of LV hypertrophy in individuals with hypertrophic cardiomyopathy (HCM). Inhibition of the Gal-3 pathway, which is currently one of the most promising novels therapeutic targets for managing myocardial fibrosis, may prevent cardiac remodeling and dysfunction In the preclinical study ( 54 ).…”
Section: Discussionmentioning
confidence: 99%